Ahmed Deedat’s contribution towards comparative study of religion - Jaffary Awang,; Aemy Elyani Mat Zain, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Ahmed Deedat is renowned as Muslim preacher in comparative religion. His viewpoints have become controversial and received many criticisms because of his messages in comparative religion’s field emphasized on theological issues such as “Is Jesus God”. Nevertheless, to date, the world has acknowledged his sterling contributions and critical thinking in clarifying the intricacies in the subject of comparative religion. Therefore, the purpose of this article is to study the contribution of Ahmed Deedat throughout his life as a Muslim preacher in comparative religion’s field. Document analysis was employed in this research to identify and evaluate the data. Based on the analysis, it was discovered that Ahmed Deedat’s lectures, writings, and dakwah movement are believed to be his earliest contributions, while gran student aspect is identified as the latest discovery in this field. The study views that this figureis not only as influential figure in the eyes of scholars all over the world but he is also influencing in terms of his thought in dakwah using comparative religion in Malaysia.